What Makes a Good City Strategy? : Competitive Cities for Jobs and Growth, Companion Paper 8 - Sivaev, Dmitry (2016)
The objective of this paper is to review and analyze the best practices in developing and implementing city strategies, particularly in lower-income environments. It reviews available evidence to formulate the list of basic criteria that good strategies should meet, discusses three key questions that city strategies should address, and suggests how the widely applied LED and CDS approaches can be improved in the future.